Precipitation hardening - Martin, J. W. (John Wilson), 1926- (Butterworth-Heinemann, 1998)
Precipitation Hardening (or age-hardening) is an important technique for the metal-using industries. The process is used to enhance the mechanical properties of a wide range of alloys, notably those based on aluminium, but also embracing some nickel and other non-ferrous alloys as well as certain steels. It is important that the mechanisms that produce this improvement in properties are understood so that the desired properties can be optimised. This book provides a thorough treatment and grounding in the subject for the student of materials science and engineering, as well as guidance, for those using the process in industry and in research. A number of excerpts from classic papers are included, which illustrate the development of precipitation hardening from being an art to a science. Precipitation Hardening (or age-hardening) is an important technique for the metal-using industries. The process is used to enhance the mechanical properties of a wide range of alloys, notably those based on aluminium, but also embracing some nickel and other non-ferrous alloys as well as certain steels. It is important that the mechanisms that produce this improvement in properties are understood so that the desired properties can be optimised. This book provides a thorough treatment and grounding in the subject for the student of materials science and engineering, as well as guidance, for those using the process in industry and in research. A number of excerpts from classic papers are included, which illustrate the development of precipitation hardening from being an art to a science.